Plan O-va Ti︠u︡lenʹi︠a︡go v zalivi︠e︡ "Terpi︠e︡nīi︠a︡" po opisi Leĭtenanta Maksimova i Michmana Gili︠a︡rovskago v 1891 g. / Kopiroval khimich. tushʹi︠u︡ S. Shlitter - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1892)
Title translation: Map of Tyuleny Island in the Gulf of Patience, according to the survey of Lieutenant Maksimov and Midshipman Gilyarovsky in 1891.; Relief shown by gradient tints. Depth shown by soundings and isolines.; "No. 383" -- bottom right margin Grayscale; 1:3,000